Productividad de Ilex paraguariensis cultivada según disponibilidad de luz - Munaretto, Nestor; Barth, Sara Regina; Fassola, Hugo Enrique; Colcombet, Luis; Gonzalez, Paola Analia; Comolli, Luis; Schegg, Esteban; Loto, Mauro (Facultad de Ciencias Forestales, UNaM. EEA Montecarlo INTA. Colegio de Ingenieros Forestales de Misiones, Coiform., 2023)
Yerba mate (Ilex paraguariensis) is one of the main income crops in North Eastern Argentina, and is cultivated under traditional open-pit management. Very little information is known about the interaction between tree species and yerba mate. On the hypothesis that shade could affect yerba mate yield and quality, in 2010 two trials have been installed: Trial 1, consociation with tree species and trial 2, interaction under different degrees of artificial shade. In trial 1, up to age seven (7), the productivity of yerba mate has not decreased. In trial 2, the performance is maintained under the different artificial shade levels studied.